Quantifying Psychosocial Impacts From Coastal Hazards for Cost-Benefit Analysis in Eastern Quebec, Canada - Boyer-Villemaire, Ursule; Kanli, Cicéron Vignon; Ledoux, Guillaume; Gosselin, Charles-Antoine; Templier, Sébastien (Frontiers in Climate, 2021)
The assessment of psychosocial impacts related to coastal hazards (erosion, submersion) has so far been mainly qualitative. As cost-benefit analysis is gaining popularity among communities to assess adaptation options in the face of increasing coastal hazards, there is a need to develop quantitative indicators to improve the inclusion of human impacts in decision-making. The project therefore aimed to suggest quantitative indicators for a cost-benefit analysis in the Lower St. Lawrence region exposed to the waters of the estuary of the St. Lawrence River in eastern Quebec, Canada. A systematic survey of five municipalities was conducted in 2019 (n = 101). In general, the prevalence of mental health was the double than that of physical health (30% vs. 14%) ; and was higher for affected respondents: 50.0% and 23.9%, against 13.5% and 5.8% for unaffected respondents. With regards to ) psychosocial impacts, the main results were that i) affected people were 2.33 more stressed in normal times than unaffected respondents and this variation increased to 3.54 during a storm surge warning ; ii) the quality of sleep of affected respondents when a storm warning is issued was 2.39 poorer than that of unaffected respondents. With regards with economic impacts, i) an additional 11% in absenteeism has been observed among respondents affected; ii) the likelihood of experiencing financial difficulties was 1.27 higher for those affected; iii) a small subgroup of affected respondents (<10) declared a mean of 400 CAD of additional health expenses. The results show that the assistance received provides little protection against stress, or even increases it, if it is mainly financial. In addition, a high degree of social isolation and living alone increases stress in the face of hazards. Thus, social capital and psychosocial assistance act as a protective factor in reducing psychosocial impacts. The probability of financial stress, on the other hand, increases in the event of maladaptation (inefficient adaptation expenditures leading to repair costs). Overall,the importance of the impacts measured justifies further economical investigation for their inclusion in the cost-benefit analysis.